Identification of circular RNAs in cardiac hypertrophy and cardiac fibrosis - Chen, Yan; Zhou, Junteng; Wei, Zisong; Cheng, Yue; Tian, Geer; Quan, Yue; Kong, Qihang; Wu, Wenchao; Liu, Xiaojing (Frontiers in Pharmacology, 2022)
Cardiac hypertrophy initially serves as an adaptive response to physiological and pathological stimuli. Sustained hypertrophy progress to pathological cardiac hypertrophy, cardiac fibrosis and ultimately lead to heart failure, one of the leading medical causes of mortality worldwide. Intervention of pathological cardiac hypertrophy can effectively reduce the occurrence of heart failure. Abundant factors, such as adrenergic, angiotensin, and endothelin (ET-1) receptors, have been shown to participate in the regulation of pathological cardiac hypertrophy. Recently, an increasing number of studies have indicated that circRNA and circRNA-miRNA–mRNA network regulation is indispensable for the posttranscriptional regulation of mRNA in cardiac hypertrophy. In our study, the morphological, cardiac function and pathological changes during cardiac hypertrophy were investigated. RNA sequencing identified 93 circRNAs that were differentially expressed in the TAC_2w group, and 55 circRNAs in the TAC_4w group compared with the sham group. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses identified several significant pathways, including hypertrophic cardiomyopathy, extracellular matrix (ECM)-receptor interaction and focal adhesion. Coexpression analyses were performed for differentially expressed circRNAs and differentially expressed mRNAs. Based on gene set enrichment analysis (GSEA), 8 circRNAs (mmu-Nfkb1_0001, mmu-Smad4_0007, mmu-Hecw2_0009, mmu-Itgbl1_0002, mmu-Lrrc2_0005, mmu-Cpeb3_0007, mmu-Ryr2_0040, and mmu-Rtn4_0001) involved in cardiac hypertrophy and cardiac fibrosis were identified. We validated some key circRNAs by qPCR. The crucial coexpression of circRNA–mRNA and its interaction with miRNA showed the possible mechanism of circRNAs in the process of cardiac dysfunction. Our results may provide promising targets for the treatment of pathological cardiac hypertrophy and fibrosis.